2002
DOI: 10.1136/gut.51.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis C virus (HCV) infection in chronic carriers of hepatitis B virus (HBV): the impact of underlying active HBV replication on persistence of HCV infection and antibody responses to HCV

Abstract: Gut 2002;51:95-99 Background and aims: The aim of this study was to assess whether underlying chronic hepatitis B virus (HBV) infection interferes with persistence of hepatitis C virus (HCV) infection and humoral immune responses to HCV in acute HCV infection. Methods: Serial sera from 12 patients with acute HCV infection (group A) and 12 hepatitis B surface antigen (HBsAg) carriers with acute HCV infection (seven anti-hepatitis B e antigen (anti-HBe) positive (group B1) and five hepatitis B e antigen (HBeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Clinical features and outcomes of patients with acute hepatitis related to concurrent HBV and HCV infection, according to HBV DNA positivity genotype type 1b HCV, in contrast to previous studies[13,16,18] that determined that >70% of patients had the genotype 1b. Further studies with a large series of patients are warranted to elucidate this observation.Like other reports…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Clinical features and outcomes of patients with acute hepatitis related to concurrent HBV and HCV infection, according to HBV DNA positivity genotype type 1b HCV, in contrast to previous studies[13,16,18] that determined that >70% of patients had the genotype 1b. Further studies with a large series of patients are warranted to elucidate this observation.Like other reports…”
mentioning
confidence: 75%
“…Studies have determined that concurrent HBV and HCV infection may be associated with a fulminant course of acute hepatitis, with severe forms of chronic liver disease and rapid progression [13][14][15][16][17][18]. Very little is known about the role and course of chronic hepatitis with acute exacerbation in patients with concurrent HBV and HCV infections.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When HBV acute superinfection occurred in HCV chronic carriers, acute HBV replication strongly inhibited the HCV genome and, compared with acute hepatitis B alone, was associated with a more severe clinical presentation (Sagnelli et al, 2002). HCV superinfection in hepatitis B surface antigen (HBsAg) chronic carriers has been poorly investigated (Romano et al, 1995;Chu et al, 1999a;Chu et al, 2002). We recently followed-up 39 consecutive patients with acute HCV infection documented by seroconversion to anti-HCV.…”
Section: Introductionmentioning
confidence: 96%
“…In this respect occult HBV infection, in particular, is often associated with accelerated progression of liver disease in HCV infected individuals [5]. While clinical studies have indicated that HCV dominates over HBV in co-infected individuals 0168 [6][7][8][9], it has also been reported that active replication of HBV can suppress the replication of HCV [10][11][12].…”
Section: Introductionmentioning
confidence: 99%